Respiratory health and disease in a UK population-based cohort of 85 year olds: The Newcastle 85+ Study. Issue 3 (5th January 2016) - Fisher, Andrew J; Yadegarfar, Mohammad E; Collerton, Joanna; Small, Therese; Kirkwood, Thomas B L; Davies, Karen; Jagger, Carol; Corris, Paul A
Abstract : Background: People aged 85 years and older are the fastest growing age group worldwide. This study assessed respiratory health, prevalence of respiratory disease and use of spirometry in respiratory diagnosis in a population-based cohort of 85 year olds to better understand respiratory health and disease in this sector of society. Methods: A single year birth-cohort of 85 year olds participated in a respiratory assessment at their home or residential institution including self-reporting of symptoms and measurement of spirometry. General practice medical records were reviewed for respiratory diagnoses and treatments. Findings: In the 845 participants, a substantial burden of respiratory disease was seen with a prevalence of COPD in medical records of 16.6% (n=140). A large proportion of the cohort had environmental exposures through past or current smoking (64.2%, n=539) and occupational risk factors (33.6%, n=269). Spirometry meeting reliability criteria was performed in 87% (n=737) of participants. In the subgroup with a diagnosis of COPD (n=123), only 75.6% (n=93) satisfied Global Initiative in Obstructive Lung Disease (GOLD) criteria for airflow obstruction, and in a healthy subgroup without respiratory symptoms or diagnoses (n=151), 44.4% (n=67) reached GOLD criteria for airflow obstruction and 43.3% (n=29) National Institute of Health and Care Excellence criteria for at least moderate COPD. Interpretation: Spirometry can be successfully performed in the very old, aged 85 years, and may help identify respiratory diseases such as COPD. However interpretation in this age group using current definitions of COPD based on spirometry indices may be difficult and lead to overdiagnosis in a healthy group with transient symptoms.